Wave storm events in the Western Mediterranean Sea over four decades. (February 2022) - Amarouche, Khalid; Akpınar, Adem; Semedo, Alvaro
Abstract: The rising intensity and recurrence of wave storm events can seriously impact navigation and coastal and offshore structures in the Western Mediterranean Sea. Therefore, the present study is focused on wave storm events in the Western Mediterranean Sea, over the last four decades. The spatial decadal variations of wave storm events are shown, considering variations in the parameters that characterise wave storms, such as significant wave height (SWH), wave storm duration, and wave storm direction. Additionally, the decadal variation in wave storm intensities is evaluated through the storm power index (SPI) and the total storm wave energy (TSWE). The study is based on a wave hindcast, developed using a calibrated SWAN model. The wave storm events are obtained based on the SWH time series for 24 325 locations, distributed over an unstructured grid, covering the entire Western Mediterranean Sea. The decadal variation in the number of wave storm events, maximum and mean wave storm duration, SPI, and TSWE were observed in large parts of the West Mediterranean Sea during the last four decades. However, variations in mean SWH during these storms are low, and do not show a real implication in the decadal changes in the wave storm intensity (SPI and TSWE). Locations of significant increasing changes in SPI and TSWE show a dependence on changes in the wave storm duration. They may be related to variations in wave storm direction in some areas. Increases in wave storm duration are mainly responsible for increases in wave storm intensities over the last decade. Highlights: Decadal characteristics of wave storm events in the W-Mediterranean are studied. Variability in storm wave frequency, duration and direction is investigated. A significant decadal change in wave storm average intensity in several locations. Dependence of the increasing wave storm intensity on wave storm duration is found.